(untitled) (Journal of Preventive and Social Medicine, 2025)
Background: The socioeconomic, political, and societal growth affects the healthcare workforce, which is seen as "vital" for health systems. In Bangladesh, over 80% of the population has one or more oral and dental diseases. This study aims to find out the motivation to become a dental surgeon choose as a career choice. Methods: This was a descriptive type of cross-sectional survey that was conducted to find out the main reason for wanting to be a dental doctor as a profession, at a selected single-center dental unit in Dhaka city. Semi-structured questionnaires were developed and delivered to the respondent. A total of 78 respondents were selected purposively from the old and new batches of 1st year BDS students. The survey was conducted from 3rd February to 1st July 2022 at Marks Medical College Dental Unit, Mirpur-14, Dhaka with consent from the principal of the institution. Results: In this study, 80.77% of respondents were female, with 51% from Dhaka, Bangladesh, and 27% from the periphery. Parents’ educational backgrounds varied, with 25.6% of fathers and 11.5% of mothers holding postgraduate degrees. Notably, 75.6% of respondents did not secure a spot at a Government University. Logistic binary regression indicated that females were three times more likely to express interest in becoming doctors than males (p<0.001). Reasons for pursuing a BDS course included fulfilling parental dreams (53.8%), and 20.5% found it more cost-effective and with a shorter duration than MBBS. Conclusion: Every person has an aim in life. But sometimes they have been forced to do another thing that they do not want to do. So, parents should understand their children’s desires. Dentistry is a challenging profession. So, those who will become dental surgeons in the future have to take all responsibilities for the patient’s wellbeing. It’s necessary to be passionate about their profession. JOPSOM 2024; 43(1): 46-49